Mechanistic analyses in kidney transplant recipients prospectively randomized to two steroid free regimen—Low dose Tacrolimus with Everolimus versus standard dose Tacrolimus with Mycophenolate Mofetil - Traitanon, Opas (PLoS One, 2019)
Calcineurin inhibitors (CNI), the cornerstone of immunosuppression after transplantation are implicated in nephrotoxicity and allograft dysfunction. We hypothesized that combined low doses of CNI and Everolimus (EVR) may result in better graft outcomes and greater tolerogenic milieu. Forty adult renal transplant recipients were prospectively randomized to (steroid free) low dose Tacrolimus (TAC) and EVR or standard dose TAC and Mycophenolate (MMF) after Alemtuzumab induction. Baseline characteristics were statistically similar. EVR levels were maintained at 3–8 ng/ml. TAC levels were 4.5±1.9 and 6.4±1.5 ng/ml in the TAC+EVR and TAC+MMF group respectively. Follow up was 14±4 and 17±5 months respectively and included protocol kidney biopsies at 3 and 12 months post-transplantation. Rejection-rate was lower in the TAC+EVR group. However patient and overall graft survival, eGFR and incidence of adverse events were similar. TAC+EVR induced expansion of CD4(+)CD25(hi)Foxp3(+) regulatory T cells as early as 3 months and expansion of IFN-γ(+)CD4(+)CD25(hi)Foxp3(+) regulatory T cells at 12 months post-transplant. Gene expression profile showed a trend toward decreased inflammation, angiogenesis and connective tissue growth in the TAC+EVR Group. Thus, greater tolerogenic mechanisms were found to be operating in patients with low dose TAC+EVR and this might be responsible for the lower rejection-rate than in patients on standard dose TAC+MMF. However, further studies with longer follow up and evaluating impact on T regulatory cells are warranted.